REKONSTRUKSI DAN REVITALISASI KOALISI DALAM SISTEM QUASI PRESIDENSIAL - Ihsan, A Bakir (Jurnal Penelitian Politik, 2011)
Coalition is not merely apower sharing Coalition requires shared commitmentfrom allparties to consistentlyrun the consensus in governing the executive branch ofgovernment through solidity ofpoliticalparty inparliamentTherefore coalition actually can be apathway to stability for government in implementing the mutually approvedpolicy It also can be a consistent balancer in controlling government As a matter offact Indonesian democraticlives coalition is based on power distribution which symbolized with position as ministry in presidential cabinetand any others structural position in government But the coalition is built without support of shared vision andmission Due to limited interest coalition would only work temporary Coalition like that seems to become themarket which merely contain unstable dailypolitical transaction